Effect of heat treatment on antirotaviral activity of bovine and ovine whey. (September 2016) - Parrón, José Antonio; Ripollés, Daniel; Pérez, María Dolores; Calvo, Miguel; Rasmussen, Jan Trige; Sánchez, Lourdes
Abstract: Rotavirus is the major cause of infectious diarrhoea in infants and children throughout the world. Several studies have indicated that some milk fractions may protect against rotavirus infection. The present study evaluates the effect of some heat treatments on the antirotaviral activity of bovine and ovine whey by an immunofluorescence assay validated in this work. Neutralising activity of diverse proteins present in whey has also been verified individually. Bovine and ovine whey, at 1 mg mL −1 protein, inhibit MA104 cells infection with bovine rotavirus strain WC3, with values of 89.2 and 76.6% inhibition, respectively. Furthermore, the inhibitory activity was influenced by temperature and duration of heat treatment. The ability of bovine and ovine whey to inhibit rotavirus infection was not affected by treatment at 75 °C for 20 s; after 85 °C for 10 min bovine and ovine whey still maintained 16.1 and 32.5%, respectively, of neutralisation activity.